2008
DOI: 10.1016/j.janxdis.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Age and racial differences in the presentation and treatment of Generalized Anxiety Disorder in primary care

Abstract: Despite the prevalence and impact of Generalized Anxiety Disorder (GAD) in the primary care setting, little is known about its presentation in this setting. The purpose of this study is to examine age and racial differences in the presentation and treatment of GAD in medical patients. Participants were recruited from one family medicine clinic and one internal medicine clinic. The prevalence of GAD was lowest for older adults. Age differences were found in the presentation of GAD, with young adults reporting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 63 publications
3
35
1
Order By: Relevance
“…As previous studies have identified age effects on reporting of anxiety and depression symptoms (Brenes et al, 2008), it might be that the use of measures that were specifically designed to measure anxiety symptoms in older adults (e.g., Pachana et al, 2007;Segal, June, Payne, Coolidge, & Yochim, 2010), would have lead to more reliable and valid results. A final question that should be specifically addressed when intervening with anxious older adults is to what extent the presence of cognitive decline interferes with the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have identified age effects on reporting of anxiety and depression symptoms (Brenes et al, 2008), it might be that the use of measures that were specifically designed to measure anxiety symptoms in older adults (e.g., Pachana et al, 2007;Segal, June, Payne, Coolidge, & Yochim, 2010), would have lead to more reliable and valid results. A final question that should be specifically addressed when intervening with anxious older adults is to what extent the presence of cognitive decline interferes with the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability analysis of the current study found Cronbach's alpha for the Positive Affect and Negative Affect scales are 0.86 and 0.85, respectively. The PANAS has been validated in older adult [29], cancer patient [8,30], and racially diverse [31,32] study samples.…”
Section: Methodsmentioning
confidence: 99%
“…Data on race differences in affect have shown mixed results. Several studies have found no significant differences in positive affect, while other data show Blacks reporting greater positive affect than Whites [31,35]. These differences may be the result of some older Blacks having better external (social support) and internal (resiliency) resources than their White counterparts.…”
Section: Race Differences In Positive Affectmentioning
confidence: 95%
“…Anxiety disorders are associated with impaired workplace performance and hefty economic costs, as well as an increased risk of cardiovascular morbidity and mortality [3,4].…”
Section: Introductionmentioning
confidence: 99%